2010
DOI: 10.1007/s00226-010-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved bondability of wax-treated wood following plasma treatment

Abstract: In this study, the impact of a plasma treatment using dielectric barrier discharge at atmospheric pressure on wax-treated beech was investigated by surface energy determination and adhesion tests. Measurements of the surface energy revealed a strong increase in surface polarity along with increased surface energy as a result of the plasma treatment, pointing to increased adhesion properties. To evaluate the adhesion properties of a polyvinyl acetate (PVAc) adhesive on beech treated with montan ester wax and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
1
5
1
1
Order By: Relevance
“…To improve the dimensional stability and durability of natural wood, various methods of modifications have been utilized (Fadl and Basta 2005;Nicholson and Hoffman 2006;Park and Wilderman 2010), including physical treatment and chemical modification (Avramidis et al 2011). Physical modification can be achieved through thermal treatment, which imparts excellent performance in water repellency and prevents the wood from deformation.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the dimensional stability and durability of natural wood, various methods of modifications have been utilized (Fadl and Basta 2005;Nicholson and Hoffman 2006;Park and Wilderman 2010), including physical treatment and chemical modification (Avramidis et al 2011). Physical modification can be achieved through thermal treatment, which imparts excellent performance in water repellency and prevents the wood from deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Avramidis et al [56] found a positive effect of plasma on the adhesion between polyvinyl acetate (PVAc) glue and beech wood pre-treated with synthetic waxes or montan-ester waxes, because a force in the sensitive peel test increased by about 50-60%. This result is not entirely in agreement with the results of our experiment, where the plasma modification of spruce wood pre-treated with fungicide not unequivocally increased the adhesion of acrylic and alkyd coatings (see Tables 2-4).…”
Section: Opinions Of Some Researchers On the Adhesion Of Coatings To Wood Surfaces Under The Influence Of Modification And Weathering Impmentioning
confidence: 99%
“…Although wood drying improves wood dimensional stability (Liu et al 2019a), it cannot meet further requirements of rose wood production. The dimensional stability can be improved by many ways (Beck et al 2017, Joffre et al 2017, Moghaddam et al 2016, Liu et al 2019b, Ozkan et al 2017) which generally can be classified into chemical modification and physical modification (Altgen et al 2016, Avamidis et al 2011, Hosseinpourpia et al 2017). Although chemical modification can obtain good results of dimensional stability, it can be harmful for human health and environment (Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%